Cytomegalovirus Colitis with Common Variable Immunodeficiency and Crohn’s Disease - Betül Ünal; Cumhur İbrahim Başsorgun; Sinem Çil Gönülcü; Aslı Uçar; Fatih Çelik; Gülsüm Özlem Elpek (Case Reports in Medicine)
Here we present an eleven-year-old male patient who had been diagnosed with common variable immunodeficiency (CVID) three years ago due to recurrent sinopulmonary infections. Two years later he had been diagnosed with Crohn’s disease (CD) due to diarrhea episodes which were unresponsive to the treatment. Depending on the active gastrointestinal bleeding and perforation he underwent total colectomy. Despite immunoglobulin and antiviral therapies, general condition of patient deteriorated and he died in the postoperative seventh day. Laboratory analysis was seronegative. CMV inclusion containing cells were detected in postmortem biopsies taken from liver, lungs, and lymph nodes.